A method for preparing high-lignified biomass-based hard carbon material by water / alcohol synergistically assisted steam explosion, hard carbon material and sodium ion battery
Through the water/alcohol synergistic auxiliary steam blasting method, the structure of high-wood biomass-based hard carbon materials is regulated, and the problem of poor sodium storage performance of traditional materials is solved, achieving high sodium storage capacity and excellent rate performance.
Patent Information
- Application Number
- CN202411640512.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Traditional high-wood biomass-based hard carbon materials have problems with low reversible capacity and poor rate performance. It is urgent to regulate the biomass-based hard carbon precursors to improve sodium storage performance.
The high-lignified biomass-based hard carbon material is prepared by water/alcohol synergistic auxiliary steam blasting method. The hydrogen bonds are formed with alcohol reagents and hemicellulose, which reduces its dissolution energy barrier, and destroys and carbonizes under high temperature and high pressure conditions to form Multi-closed pore structure.
The sodium storage capacity and rate performance of high-lignified biomass-based hard carbon materials is significantly improved, and the process is simple and the production cost is low, so there is no need to introduce other pore-forming agents or activators.
Smart Images

Figure CN119143114B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion battery materials, and in particular relates to a method for preparing a high-lignified biomass-based hard carbon material by water / alcohol-assisted steam explosion, the hard carbon material and a sodium ion battery. Background Art
[0002] Sodium-ion batteries are considered to be one of the most promising energy storage systems due to their low cost, abundant sodium resources and good safety performance. As a carbon-based negative electrode material, hard carbon materials have great commercial application potential due to their simple preparation process, high energy density and excellent sodium storage capacity. Among them, biomass-based hard carbon raw materials are widely available, low-cost and have rich pore structures, and are increasingly attracting attention.
[0003] At present, biomass-based hard carbon precursors mainly include coconut shells, bamboo, straw, etc., which are all high-lignified biomass with high lignin content. Traditional high-lignified biomass-based hard carbon materials have problems such as low reversible capacity and poor rate performance. It is urgent to regulate the structure of biomass-based hard carbon precursors to improve the sodium storage performance of high-lignified biomass-based hard carbon materials.
[0004] Steam explosion is an efficient and low-energy processing technology that can destroy the structure of biomass and hydrolyze organic macromolecules. It has begun to be applied in the preparation of hard carbon materials. For example, in the patent document with application number CN202411281017.9, the biomass powder is directly steam-exploded in a steam explosion kettle. Although it can destroy the biomass structure to a certain extent, the degree of destruction is still limited and needs further improvement. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a method for preparing high-lignified biomass-based hard carbon material by water / alcohol synergistically assisted steam explosion, a hard carbon material and a sodium ion battery.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0007] A method for preparing a high-lignified biomass-based hard carbon material by water / alcohol synergistically assisted steam explosion comprises the following steps:
[0008] (1) soaking, washing, drying and crushing high-lignified biomass to obtain high-lignified biomass powder, wherein the high-lignified biomass is selected from at least one of bamboo, reed, poplar and willow;
[0009] (2) Soaking the biomass powder in water and an alcohol reagent; the mass ratio of the water to the alcohol reagent is 1:1 to 9:1; the alcohol reagent is one of methanol, ethanol, glycerol, and isopropanol; the mass ratio of the water to the alcohol reagent needs to be controlled within this range, otherwise, there will be more water and less alcohol, and the effect of alcohol on hemicellulose will be weakened, which is mainly reflected in the direct dissolution of hemicellulose and the reduction of the dissolution energy barrier of hemicellulose, resulting in weak damage to the structure; if there is less water and more alcohol, the alcohol reagent is easy to volatilize, and the damage to the structure is too strong, resulting in the graphite domain prepared in the carbonization process being too short, the enclosed closed pore size is too small, and the sodium storage performance is poor;
[0010] (3) The material after step (2) is supplemented with water and alcohol reagents to a solid content of 50% to 90%, and then treated at a steam pressure of 1 MPa to 3 MPa and a temperature of 150°C to 280°C for 1 min to 60 min, followed by pressure release and explosion. The steam explosion method is mainly divided into two processes: first, under high temperature and high pressure conditions, hemicellulose and part of lignin are degraded to reduce the degree of polymerization of biomass; then, the explosion (rapid pressure release) process is performed to break and expand the original fiber structure, further reducing the degree of polymerization of biomass. Steam explosion can effectively destroy the highly lignified biomass structure, reduce the degree of polymerization of organic molecules, facilitate structural winding during carbonization, form more closed-cell structures, and improve sodium storage capacity and rate performance.
[0011] (4) The steam explosion product after step (3) is subjected to low-temperature carbonization, impurity removal treatment, high-temperature carbonization, and crushing and classification in sequence to obtain a high-lignified biomass-based hard carbon material.
[0012] The above-mentioned method of preparing highly lignified biomass-based hard carbon materials by water / alcohol synergistically assisted steam explosion controls the solid content of the material subjected to steam explosion to be 50% to 90%. The solid content cannot be too high, otherwise the ratio of water and alcohol reagents is too low, too little liquid enters the biomass, and during the explosion process, the mechanical force generated is too low, and the destruction of the biomass structure during the steam explosion process is weak. The solid content cannot be too low, otherwise there is too much liquid, resulting in the inability to fully gasify the internal liquid, and hindering the penetration of the gas phase, resulting in weak destruction of the biomass structure.
[0013] In the above-mentioned method for preparing highly lignified biomass-based hard carbon materials by water / alcohol synergistically assisted steam explosion, in step (2), under high temperature and high pressure conditions, alcohol reagents can form hydrogen bonds with hydroxyl groups in hemicellulose, as shown in equation (1), weakening the hydrogen bonding forces within and between hemicellulose molecules and promoting the dissolution of hemicellulose. The addition of alcohol reagents can reduce the dissolution energy barrier of hemicellulose and accelerate the dissolution of hemicellulose. Under high pressure conditions, water and alcohol reagents can penetrate deeper into the biomass, effectively break glycosidic bonds, and promote the expansion of the biomass structure. During the explosion process, water and alcohol reagents can quickly gasify and destroy the biomass structure.
[0014]
[0015] Among them, ··· represents hydrogen bonds. This process is a reversible physical process without the breaking and formation of chemical bonds. The hydrogen bonds formed by the action of alcohol and hemicellulose weaken the forces within / between hemicellulose molecules and promote the dissolution of hemicellulose.
[0016] The addition of alcohol reagents can reduce the energy barrier of the hemicellulose dissolution reaction, making the hemicellulose easier to dissolve and increasing the reaction rate. The mass ratio of water to alcohol reagents should be controlled at 1:1~9:1. If the proportion of alcohol reagents is too large, hemicellulose will dissolve too much; if the proportion of alcohol reagents is too small, hemicellulose will dissolve too little.
[0017] In this application, the NREL method was used to determine the content of cellulose, lignin, and hemicellulose in biomass and analyze the dissolution degree of hemicellulose. The dissolution ratio of hemicellulose should be controlled at 30% to 70%. The stronger the dissolution degree of hemicellulose, the more water and alcohol reagents penetrate into the biomass, and the stronger the structural damage during steam explosion; the weaker the dissolution degree of hemicellulose, the less water and alcohol reagents penetrate into the biomass, and the weaker the structural damage during steam explosion.
[0018] The weight average molecular weight Mw is the statistical average molecular weight by mass, which is the average molecular weight per unit weight. For details, see formula (I). The degree of biomass structural damage is expressed by the weight average molecular weight Mw. Biomass is mainly composed of cellulose, lignin, hemicellulose, sugars and other components. Steam explosion will shorten the long chain of organic components and reduce the relative molecular mass Mw. i , thereby reducing the weight average molecular weight. Mw should be controlled between 85,000 and 110,000. The larger the Mw, the weaker the destruction of the biomass structure, the longer the graphite domain of the prepared hard carbon material, and the less closed-pore structure; the smaller the Mw, the stronger the destruction of the biomass structure, the shorter the graphite domain of the prepared hard carbon material, and the less closed-pore structure.
[0019]
[0020] Wherein, Mw represents the weight average molecular weight, m i is the molecular mass, M i is the relative molecular mass, w i is the quality score.
[0021] The closed-cell structure is a key factor affecting the platform capacity of hard carbon materials. The more closed-cell structures there are, the larger the platform capacity, the higher the reversible capacity, and the better the rate performance; the fewer closed-cell structures there are, the smaller the platform capacity, the lower the reversible capacity, and the worse the rate performance.
[0022] In the above-mentioned method for preparing high-lignified biomass-based hard carbon materials by water / alcohol synergistically assisted steam explosion, preferably, in step (1), the soaking time is 1 h-8 h, and the soaking temperature is 20°C~90°C; the drying temperature is 50°C-100°C, and the drying time is 6 h-24 h.
[0023] In the above-mentioned method for preparing high-lignified biomass-based hard carbon materials by water / alcohol synergistically assisted steam explosion, preferably, in step (4), the temperature of the low-temperature carbonization is 400°C~800°C, and the insulation time is 1 h~4 h; the low-temperature carbonization is carried out in a protective atmosphere, and the protective atmosphere is at least one of nitrogen and argon, and the gas flow rate of the protective atmosphere is 0.1 L / h~4 L / h.
[0024] In the above-mentioned method for preparing high-lignified biomass-based hard carbon materials by water / alcohol synergistically assisted steam explosion, preferably, in step (4), the high-temperature carbonization temperature is 1000°C~1600°C, and the insulation time is 1 h~4 h; the high-temperature carbonization is carried out in a protective atmosphere, and the protective atmosphere is at least one of nitrogen and argon, and the gas flow rate of the protective atmosphere is 0.1 L / h~4 L / h.
[0025] In the above-mentioned method for preparing high-lignified biomass-based hard carbon materials by water / alcohol synergistically assisted steam explosion, preferably, in step (4), the impurity removal treatment adopts chemical impurity removal, and the impurity elements are removed by alkali leaching and acid leaching. The alkali leaching uses one or more mixed solutions of sodium hydroxide, potassium hydroxide, and ammonia water, and the acid leaching uses one or more mixed solutions of sulfuric acid, hydrochloric acid, nitric acid, and hydrofluoric acid.
[0026] As a general inventive concept, the present invention also provides a high-lignified biomass-based hard carbon material prepared by the above method, wherein the particle size D50 of the high-lignified biomass-based hard carbon material is 2 μm to 10 μm, and the specific surface area is 5 m 2 / g~10 m 2 / g, and the average pore size is 6 nm~10 nm.
[0027] As a general inventive concept, the present invention also provides a sodium ion battery, comprising the above-mentioned high lignified biomass-based hard carbon material or the high lignified biomass-based hard carbon material prepared by the above-mentioned method.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention adopts water / alcohol synergistically assisted steam explosion to prepare high lignification biomass-based hard carbon materials. During the steam explosion process, water and alcohol reagents are selected. Alcohol reagents can form hydrogen bonds with hydroxyl groups in hemicellulose, weakening the hydrogen bonding forces within and between hemicellulose molecules, and can also reduce the dissolution energy barrier of hemicellulose, thereby promoting the dissolution of hemicellulose. Water and alcohol reagents can penetrate deeper into the biomass and effectively break the glycosidic bonds. Steam explosion quickly gasifies, destroys the biomass structure, reduces the degree of polymerization, and facilitates the winding of the carbon layer during the carbonization process to form more closed-pore structures. When it is used as a negative electrode material for sodium ion batteries, it has the advantages of high sodium storage capacity, high reversible capacity, and excellent rate performance.
[0030] (2) The process of the present invention does not require the introduction of other chemical reagents such as pore-forming agents and activators, and the process is simple and the production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM image of the biomass-based hard carbon material prepared in Example 1 of the present invention.
[0032] Figure 2 This is a TEM image of the biomass-based hard carbon material prepared in Example 1 of the present invention.
[0033] Figure 3 It is a TEM image of the biomass-based hard carbon material prepared in Comparative Example 1 of the present invention.
[0034] Figure 4 This is a TEM image of the biomass-based hard carbon material prepared in Comparative Example 3 of the present invention.
[0035] Figure 5 This is a graph of the electrochemical performance of sodium ion batteries prepared from biomass-based hard carbon materials prepared in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION
[0036] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0037] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0039] Embodiment 1:
[0040] A method for preparing a highly lignified biomass-based hard carbon material by water / alcohol synergistically assisted steam explosion of the present invention comprises the following steps:
[0041] (1) Raw material processing: soak bamboo in distilled water for 2 h, wash, dry at 80 ° C for 20 h, and pre-crush to obtain high-lignified biomass powder; soak the high-lignified biomass powder in a mixed solution of water and glycerol in a mass ratio of 7:1 for 12 h, filter, and add liquid to the filter residue until the solid content is 80%. The added liquid is a mixed solution of water and glycerol in a mass ratio of 7:1 to obtain a biomass solution;
[0042] (2) Steam explosion: the biomass solution treated in step (1) is transferred to a reactor, water vapor is introduced and the temperature is increased, and the biomass solution is treated at 2.0 MPa and 220° C. for 30 min, then the pressure is released and the biomass solution is exploded and dried to obtain a steam exploded product;
[0043] (3) Low-temperature carbonization: The steam explosion product was heated to 600 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonization product was obtained.
[0044] (4) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 6 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1.5 mol / L and hydrofluoric acid having a concentration of 2 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product;
[0045] (5) High-temperature carbonization: The impurity-removed product was heated to 1500°C at a heating rate of 3°C / min under the protection of argon gas for high-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained.
[0046] (6) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain biomass-based hard carbon materials.
[0047] The SEM image of the biomass-based hard carbon material prepared in this example is as follows: Figure 1 As shown, the prepared hard carbon material has an irregular shape and an obvious porous structure on the surface of the sample.
[0048] The TEM image of the biomass-based hard carbon material prepared in this example is as follows: Figure 2 As shown, the prepared hard carbon material has short graphite domains and rich closed-pore structure, which indicates that the steam explosion pretreatment effectively destroys the biomass structure.
[0049] In this example, the Mw of the biomass after steam explosion was 91473, and the hemicellulose content was 3.52%. The degree of structural destruction and hemicellulose dissolution was relatively strong.
[0050] The particle size D50 of the biomass-based hard carbon material prepared in this example is 6.125 μm, and the specific surface area is 8.210 m 2 / g, and the average pore size is 8.973 nm.
[0051] The hard carbon material prepared in this example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and its electrochemical performance was measured:
[0052] The hard carbon material powder prepared in this embodiment is mixed with acetylene black and PVDF in a mass ratio of 90:5:5, and then a proper amount of organic solvent NMP is added to grind to form a slurry, and then the grinded slurry is evenly coated on the current collector copper foil, and after drying, it is cut into circular pole pieces. The pole pieces are dried at 120°C for 6 hours under vacuum conditions and then transferred to a glove box for use.
[0053] The simulated battery was assembled in a glove box with an Ar atmosphere, using metallic sodium as the counter electrode and 1 mol of NaPF6 dissolved in 1 L of ethylene glycol dimethyl ether as the electrolyte to assemble a CR2032 button cell. The constant current charge and discharge mode was used to perform charge and discharge tests at a current density of 0.1C. Figure 5 As shown, under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity is 330.90 mAh / g, the first-week coulombic efficiency is 87.01%, and the capacity is 250.37 mAh / g at a current density of 5.0C.
[0054] Embodiment 2:
[0055] A method for preparing a highly lignified biomass-based hard carbon material by water / alcohol synergistically assisted steam explosion of the present invention comprises the following steps:
[0056] (1) Raw material processing: Soak the bamboo in distilled water for 5 h, wash it, dry it at 80 °C for 18 h, and pre-crush it to obtain high-lignified biomass powder;
[0057] (2) Soaking the high-lignified biomass powder in a mixed solution of water and glycerol in a mass ratio of 7:1 for 12 hours, adding liquid to the filter residue until the solid content is 90%, and the added liquid is a mixed solution of water and glycerol in a mass ratio of 7:1 to obtain a biomass solution;
[0058] (3) Steam explosion: the biomass treated in step (2) is transferred to a reactor, steam is introduced and the temperature is increased, and the biomass is treated at 1.9 MPa and 200°C for 30 min, the pressure is released and the explosion is performed, and the steam explosion product is obtained by drying;
[0059] (4) Low-temperature carbonization: The steam explosion product was heated to 500 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonization product was obtained.
[0060] (5) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 5 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1.5 mol / L and hydrofluoric acid having a concentration of 2 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product;
[0061] (6) High-temperature carbonization: The impurity-removed product was subjected to high-temperature carbonization at a heating rate of 3°C / min to 1450°C under the protection of argon gas. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained.
[0062] (7) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain biomass-based hard carbon materials.
[0063] In this example, the Mw of the biomass after steam explosion is 95430, and the hemicellulose content is 3.61%. The degree of structural destruction and hemicellulose dissolution is relatively strong.
[0064] The particle size D50 of the biomass-based hard carbon material prepared in this example is 6.317 μm, and the specific surface area is 8.219 m 2 / g, and the average pore size is 9.163 nm.
[0065] The biomass-based hard carbon material of this embodiment is used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test is carried out, and the preparation process and test method are the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity is 326.70 mAh / g, the first-week coulomb efficiency is 86.93%, and the capacity is 239.76 mAh / g at a current density of 5.0C.
[0066] Comparative Example 1:
[0067] The difference between this comparative example and Example 1 is that there is no steam explosion treatment, and the remaining steps are the same as those in Example 1. The specific steps are as follows:
[0068] (1) Raw material processing: soak bamboo in distilled water for 2 h, wash, dry at 80 °C for 20 h, and pre-crush to obtain high-lignified biomass powder; soak the lignified biomass powder in a mixed solution of water and propylene glycol with a mass ratio of 7:1 for 12 h, filter and dry;
[0069] (2) Low-temperature carbonization: The treated bamboo was heated to 600 °C at a heating rate of 5 °C / min under the protection of argon gas for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, the low-temperature carbonization product was obtained.
[0070] (3) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 6 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1.5 mol / L and hydrofluoric acid having a concentration of 2 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product;
[0071] (4) High-temperature carbonization: The impurity-removed product was heated to 1500°C at a heating rate of 3°C / min under the protection of argon gas for high-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained.
[0072] (5) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain biomass-based hard carbon materials.
[0073] In this comparative example, the Mw of the biomass after raw material treatment is 152374, the content of hemicellulose is 13.40%, and the degree of structural destruction and hemicellulose dissolution is extremely weak.
[0074] The particle size D50 of the biomass-based hard carbon material prepared in this comparative example is 6.249 μm, and the specific surface area is 4.793 m 2 / g, and the average pore size is 6.037nm.
[0075] The TEM image of the biomass-based hard carbon material prepared in this comparative example is as follows Figure 3 As shown, the prepared hard carbon material has longer graphite domains and less closed-pore structures.
[0076] The biomass-based hard carbon material of this comparative example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test was carried out. The preparation process and test method were the same as those in Example 1. The results are as follows Figure 5 As shown: under the conditions of discharge cut-off voltage of 0.01V and charge cut-off voltage of 2.0V, the reversible specific capacity is 291.97 mAh / g, the coulombic efficiency in the first week is 84.10%, and the capacity is 183.44 mAh / g at a current density of 5.0C.
[0077] Comparative Example 2:
[0078] The difference between this comparative example and Example 1 is that water and glycerol are not used for treatment, and the remaining steps are the same as those in Example 1. The specific steps are as follows:
[0079] (1) Raw material processing: soak the bamboo in distilled water for 2 h, wash it, dry it at 80 °C for 20 h, and pre-crush it;
[0080] (2) Steam explosion: The pre-crushed biomass is transferred to a reactor, steam is introduced and the temperature is increased. The biomass is treated at 2.0 MPa and 220 °C for 30 min, and then the pressure is released and exploded. The biomass is dried to obtain the steam-exploded product.
[0081] (3) Low-temperature carbonization: The steam explosion product was heated to 600 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonization product was obtained.
[0082] (4) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 6 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1.5 mol / L and hydrofluoric acid having a concentration of 2 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product;
[0083] (5) High-temperature carbonization: The impurity-removed product was heated to 1500°C at a heating rate of 3°C / min under the protection of argon gas for high-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained.
[0084] (6) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain biomass-based hard carbon materials.
[0085] In this comparative example, the Mw of the biomass after steam explosion was 132340, the content of hemicellulose was 11.76%, and the degree of structural destruction and hemicellulose dissolution was relatively weak.
[0086] The particle size D50 of the biomass-based hard carbon material prepared in this comparative example is 6.011 μm, and the specific surface area is 6.474 m 2 / g, and the average pore size is 6.780 nm.
[0087] The biomass-based hard carbon material of this comparative example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test was carried out, and the preparation process and the test method were the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity was 310.76 mAh / g, the first-week coulomb efficiency was 85.01%, and the capacity was 220.30 mAh / g at a current density of 5.0C.
[0088] Comparative Example 3:
[0089] The difference between this comparative example and Example 1 is that water treatment is used instead of glycerol treatment, and the remaining steps are the same as those in Example 1. The specific steps are as follows:
[0090] (1) Raw material processing: soak bamboo in distilled water for 2 h, wash, dry at 80 °C for 20 h, and pre-crush to obtain high-lignified biomass powder; soak the lignified biomass powder in water for 12 h, filter, and add water to the filter residue to a solid content of 80% to obtain a biomass solution;
[0091] (2) Steam explosion: The treated biomass solution is transferred to a reactor, steam is introduced and the temperature is increased. After treatment at 2.0 MPa and 220 °C for 30 min, the pressure is released and the biomass solution is exploded and dried to obtain a steam-exploded product.
[0092] (3) Low-temperature carbonization: The steam explosion product was heated to 600 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonization product was obtained.
[0093] (4) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 6 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1.5 mol / L and hydrofluoric acid having a concentration of 2 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product;
[0094] (5) High-temperature carbonization: The impurity-removed product was heated to 1500°C at a heating rate of 3°C / min under the protection of argon gas for high-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained.
[0095] (6) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain biomass-based hard carbon materials.
[0096] In this comparative example, the Mw of the biomass after steam explosion was 120367, the content of hemicellulose was 8.46%, and the degree of structural destruction and hemicellulose dissolution was relatively weak.
[0097] The particle size D50 of the biomass-based hard carbon material prepared in this comparative example is 5.974 μm, and the specific surface area is 6.966 m 2 / g, and the average pore size is 7.178 nm.
[0098] The TEM image of the biomass-based hard carbon material prepared in this comparative example is as follows Figure 4 As shown, compared with the TEM of the hard carbon material prepared in Example 1, the prepared hard carbon material has longer graphite domains and less closed-pore structures.
[0099] The biomass-based hard carbon material of this comparative example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test was carried out, and the preparation process and the test method were the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity was 323.55 mAh / g, the first-week coulomb efficiency was 86.04%, and the capacity was 239.60 mAh / g at a current density of 5.0C.
[0100] Comparative Example 4:
[0101] The difference between this comparative example and Example 1 is that this comparative example only uses glycerol for treatment, and does not use water for treatment. The remaining steps are the same as those in Example 1. The specific steps are as follows:
[0102] (1) Raw material processing: soak the bamboo in distilled water for 2 h, wash, dry at 80 °C for 20 h, pre-crush, soak in glycerol for 12 h, filter, and add glycerol to the residue until the solid content is 80% to obtain a biomass solution;
[0103] (2) Steam explosion: the biomass solution treated in step (1) is transferred to a reactor, water vapor is introduced and the temperature is increased, and the biomass solution is treated at 2.0 MPa and 220° C. for 30 min, then the pressure is released and the biomass solution is exploded and dried to obtain a steam exploded product;
[0104] (3) Low-temperature carbonization: The steam explosion product was heated to 600 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonization product was obtained.
[0105] (4) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 6 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1.5 mol / L and hydrofluoric acid having a concentration of 2 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product;
[0106] (5) High-temperature carbonization: The impurity-removed product was heated to 1500°C at a heating rate of 3°C / min under the protection of argon gas for high-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained.
[0107] (6) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain biomass-based hard carbon materials.
[0108] In this comparative example, the Mw of the biomass after steam explosion was 107490, the content of hemicellulose was 6.47%, and the degree of structural destruction and hemicellulose dissolution was average.
[0109] The particle size D50 of the biomass-based hard carbon material prepared in this comparative example is 5.875 μm, and the specific surface area is 7.203 m 2 / g, and the average pore size is 7.318 nm.
[0110] The biomass-based hard carbon material of this comparative example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test was carried out, and the preparation process and the test method were the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity was 319.45 mAh / g, the first-week coulomb efficiency was 85.84%, and the capacity was 230.31 mAh / g at a current density of 5.0C.
[0111] Comparative Example 5:
[0112] The difference between this comparative example and Example 1 is that the solid content of biomass during steam explosion is different, and the remaining steps are the same as those in Example 1. The specific steps are as follows:
[0113] (1) Raw material processing: soak bamboo in distilled water for 2 h, wash, dry at 80 ° C for 20 h, and pre-crush to obtain high-lignified biomass powder; soak the lignified biomass powder in a mixed solution of water and glycerol in a mass ratio of 7:1 for 12 h, filter, and add liquid to the filter residue to a solid content of 20%. The added liquid is a mixed solution of water and glycerol in a mass ratio of 7:1 to obtain a biomass solution;
[0114] (2) Steam explosion: The treated biomass solution is transferred to a reactor, steam is introduced and the temperature is increased. After treatment at 2.0 MPa and 220 °C for 30 min, the biomass solution is exploded and dried to obtain a steam-exploded product.
[0115] (3) Low-temperature carbonization: The steam explosion product was heated to 600 °C under the protection of argon at a heating rate of 5 °C / min for low-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a low-temperature carbonization product was obtained.
[0116] (4) Impurity removal treatment: The low-temperature carbonization product is first subjected to alkaline leaching treatment with a sodium hydroxide solution having a concentration of 6 mol / L for 5 h; then subjected to acid leaching treatment with a mixed solution of hydrochloric acid having a concentration of 1.5 mol / L and hydrofluoric acid having a concentration of 2 mol / L for 5 h to remove impurity elements and obtain an impurity-removed product;
[0117] (5) High-temperature carbonization: The impurity-removed product was heated to 1500°C at a heating rate of 3°C / min under the protection of argon gas for high-temperature carbonization. The carbonization holding time was 2 h, and the argon gas flow rate was 0.3 L / h. After cooling to room temperature, a high-temperature carbonized product was obtained.
[0118] (6) Crushing and classification: The high-temperature carbonization product is subjected to air flow crushing to obtain biomass-based hard carbon materials.
[0119] In this comparative example, the Mw of the biomass after steam explosion was 110731, the hemicellulose content was 7.73%, and the degree of structural destruction and hemicellulose dissolution was average.
[0120] The particle size D50 of the biomass-based hard carbon material prepared in this comparative example is 6.487 μm, and the specific surface area is 7.297 m 2 / g, and the average pore size is 7.011 nm.
[0121] The biomass-based hard carbon material of this comparative example was used as the active material of the negative electrode of the sodium ion battery for the preparation of the sodium ion battery, and the electrochemical charge and discharge test was carried out, and the preparation process and the test method were the same as those in Example 1. The results are as follows: under the conditions of a discharge cut-off voltage of 0.01 V and a charge cut-off voltage of 2.0 V, the reversible specific capacity was 315.30 mAh / g, the first-week coulomb efficiency was 85.29%, and the capacity was 225.87 mAh / g at a current density of 5.0C.
[0122] It can be seen from the above examples and comparative examples that the biomass-based hard carbon material prepared by the present invention is used for the preparation of sodium ion batteries, and has excellent reversible specific capacity, first-week coulombic efficiency and rate performance. When the biomass-based hard carbon material prepared in Example 1 is used in a sodium ion battery, the electrochemical performance is the best, with a reversible specific capacity of 330.90 mAh / g, a first-week coulombic efficiency of 87.01%, and a capacity of 250.37 mAh / g at a current density of 5.0C.
[0123] Compared with Example 1, Comparative Example 1 has no steam explosion treatment, and the graphite domain of the hard carbon material prepared from high lignified biomass is longer, the closed-cell structure is scarce, and the electrochemical performance is extremely poor; Comparative Example 2 does not use water and alcohol reagents for treatment, and the degree of damage to the precursor structure by steam explosion is poor, the graphite domain of the prepared hard carbon material is slightly longer, the closed-cell structure is scarce, and the electrochemical performance is poor; Comparative Example 3 only uses water treatment, and does not use alcohol reagents for treatment. The degree of damage to the precursor structure by steam explosion is poor, and the graphite domain of the prepared hard carbon material is slightly longer, the closed-cell structure is scarce, and the electrochemical performance is poor. The pore structure is relatively scarce, and the electrochemical performance is poor; in Comparative Example 4, only alcohol reagents are used for treatment, and water treatment is not used. The degree of destruction of the precursor structure by steam explosion is poor, the graphite domain of the prepared hard carbon material is slightly long, the closed-pore structure is relatively scarce, and the electrochemical performance is poor; in Comparative Example 5, the biomass solid content during the steam explosion process is low, resulting in the inability to fully gasify the internal liquid and hindering the penetration of the gas phase, resulting in weak destruction of the biomass structure, the graphite domain of the prepared hard carbon material is slightly long, the closed-pore structure is relatively scarce, and the electrochemical performance is poor.
[0124] The present invention adopts biomass raw materials with high lignification structure as precursors, and combines water and alcohol reagents to assist steam explosion. The addition of alcohol reagents weakens the hydrogen bonding forces within and between hemicellulose molecules, reduces the dissolution energy barrier of hemicellulose, promotes the dissolution of hemicellulose, strengthens the degree of damage to the biomass structure caused by steam explosion, reduces the polymerization degree of the precursor, facilitates the winding of the carbon layer during the carbonization process, forms more closed-cell structures, and is beneficial to improving the sodium storage capacity and rate performance. Therefore, the biomass-based hard carbon material prepared by the present invention exhibits excellent electrochemical properties when used in sodium ion batteries.
Claims
1. A sodium ion battery, characterized in that: The invention relates to a highly lignified biomass-based hard carbon material prepared by the following method for preparing a highly lignified biomass-based hard carbon material by water / alcohol synergistically assisted steam explosion, wherein the method for preparing a highly lignified biomass-based hard carbon material by water / alcohol synergistically assisted steam explosion comprises the following steps: (1) soaking, washing, drying and crushing high-lignified biomass to obtain high-lignified biomass powder, wherein the high-lignified biomass is selected from at least one of bamboo, reed, poplar and willow; (2) adding the high lignified biomass powder into water and an alcohol reagent and soaking the powder; the mass ratio of the water to the alcohol reagent is 1:1 to 9:1, and the alcohol reagent is at least one of methanol, ethanol, glycerol, and isopropanol; (3) Add water and alcohol reagent to the material after step (2) until the solid content is 50% to 90%, and then treat it under the conditions of steam pressure of 1 MPa to 3 MPa and temperature of 150°C to 280°C for 1 min to 60 min, and then release the pressure and blast; (4) The blasting product after step (3) is subjected to low-temperature carbonization, impurity removal, high-temperature carbonization, and crushing and classification in sequence to obtain a high-lignified biomass-based hard carbon material.
2. The sodium ion battery according to claim 1, characterized in that In step (1), the soaking time is 1 h to 8 h, and the soaking temperature is 20° C. to 90° C.; the drying temperature is 50° C. to 100° C., and the drying time is 6 h to 24 h.
3. The sodium ion battery according to claim 1, characterized in that In step (4), the temperature of the low-temperature carbonization is 400°C to 800°C, and the holding time is 1 h to 4 h; the low-temperature carbonization is carried out in a protective atmosphere, the protective atmosphere is at least one of nitrogen and argon, and the gas flow rate of the protective atmosphere is 0.1 L / h to 4 L / h.
4. The sodium ion battery according to claim 1, characterized in that In step (4), the temperature of the high-temperature carbonization is 1000°C~1600°C, and the holding time is 1 h~4 h; the high-temperature carbonization is carried out in a protective atmosphere, the protective atmosphere is at least one of nitrogen and argon, and the gas flow rate of the protective atmosphere is 0.1 L / h~4 L / h.
5. The sodium ion battery according to claim 1, characterized in that The particle size D50 of the high-lignified biomass-based hard carbon material is 2 μm to 10 μm, and the specific surface area is 5 m 2 / g~10 m 2 / g, and the average pore size is 6 nm~10 nm.
Citation Information
Patent Citations
Biomass hard carbon material and preparation method and application of precursor of biomass hard carbon material
CN118790980A
Preparation method of straw coal
CN106635231A